T-Cell Immunodeficiencies With Congenital Alterations of Thymic Development: Genes Implicated and Differential Immunological and Clinical Features - Giardino, Giuliana; Borzacchiello, Carla; De Luca, Martina; Romano, Roberta; Prencipe, Rosaria; Cirillo, Emilia; Pignata, Claudio (Frontiers in Immunology, 2020)
Combined Immunodeficiencies (CID) are rare congenital disorders characterized by defective T-cell development that may be associated with B- and NK-cell deficiency. They are usually due to alterations in genes expressed in hematopoietic precursors but in few cases, they are caused by impaired thymic development. Athymia was classically associated with DiGeorge Syndrome due to TBX1 gene haploinsufficiency. Other genes, implicated in thymic organogenesis include FOXN1, associated with Nude SCID syndrome, PAX1, associated with Otofaciocervical Syndrome type 2, and CHD7, one of the genes implicated in CHARGE syndrome. More recently, chromosome 2p11.2 microdeletion, causing FOXI3 haploinsufficiency, has been identified in 5 families with impaired thymus development. In this review, we will summarize the main genetic, clinical and immunological features related to the abovementioned genes mutations. We will also focus on different therapeutic approaches to treat SCID in these patients.